Aggregate Productivity Growth in Indian Manufacturing: An Application of Domar Aggregation - Deb Kusum Das; Gunajit Kalita (Indian Council for Research on International Economic Relations (ICRIER), 2009)
Productivity growth in Indian manufacturing is an important driver of overall growth, yet the issues related to its measurement have still not been resolved. The issue of how to compute an aggregate productivity measure holds significance for two reasons: one, the productivity of a firm should reflect the productivity of the lower levels, which comprise the aggregate; and two, aggregate productivity should also emphasize the importance of inter-industry transactions in an analysis of productivity growth. Contributions from Domar (1961), Hulten (1978) and Jorgenson et al. (1987) have addressed the issue of measuring aggregate productivity. We have made an attempt to compute the aggregate productivity growth using the Domar aggregation technique. Building up from the Total Factor Productivity Growth (TFPG) estimates for 3-digit industries, we have used Domar weights to computed total factor productivity (TFP) growth for selected 10, 2-digit industries for the period 1980-2000. Comparing the estimates based on the Domar aggregation technique with those based on the traditional aggregate value added approach, we observe that the preferred estimates are about half of that obtained by the traditional aggregate value added method. This holds immense significance for any underlying productivity numbers.
Keywords: D24; L6; O47; O53; 330; Productivity growth; Domar aggregation; aggregate value added; Indian manufacturing; Produktivität; Industrie; Indien